GENDER-MARKED SIMILES IN ENGLISH: A STUDY OF GENDER REPRESENTATION THROUGH COMPARATIVE EXPRESSIONS - Torebaeva Firuza Kidirbaevna (International Journal of Literature and Language Studies, 2026)
Abstract: Gender-marked similes in English reflect cultural attitudes, social expectations, and historical stereotypes associated with masculinity and femininity. Similes, as figurative expressions comparing two unlike objects through the use of “like” or “as,” often carry implicit gender meanings that shape linguistic perception. Expressions such as “as brave as a lion” or “as gentle as a lamb” frequently become associated with male and female characteristics respectively, reinforcing traditional gender roles in communication. This article examines the linguistic structure, semantic features, and sociocultural significance of gender-marked similes in English. It explores how such expressions contribute to the preservation of stereotypes, influence interpersonal communication, and reflect broader societal ideologies. The study also analyzes examples from literature, everyday speech, and media discourse to demonstrate how gender associations are embedded in figurative language. Special attention is given to the evolution of similes in modern English and the growing tendency toward gender-neutral language. The article argues that while many traditional similes continue to reproduce patriarchal values, contemporary discourse increasingly challenges rigid gender distinctions. Through semantic and stylistic analysis, the research highlights the importance of critical awareness in the interpretation and usage of figurative expressions.